CACNA1H antibodies associated with headache with neurological deficits and cerebrospinal fluid lymphocytosis (HaNDL). - Kürtüncü, M; Kaya, D; Zuliani, L; Erdağ, E; Içöz, S; Uğurel, E; Cavuş, F; Ayşit, N; Birişik, O; Vincent, A; Eraksoy, M; Vural, B; et al. (2013)
BACKGROUND: Patients with the syndrome of headache with neurological deficits and lymphocytosis (HaNDL) typically present with recurrent and temporary attacks of neurological symptoms and cerebrospinal fluid lymphocytosis. AIM AND METHODS: To identify potential HaNDL-associated antibodies directed against neuronal surface and/or synapse antigens, sera of four HaNDL patients and controls were screened with indirect immunohistochemistry, immunofluorescence, cell-based assay, radioimmunoassay, protein macroarray and enzyme-linked immunosorbent assay (ELISA). RESULTS: Although HaNDL sera did not yield antibodies to any of the well-characterized neuronal surface or synapse antigens, protein macroarray and ELISA studies showed high-titer antibodies to a subunit of the T-type voltage-gated calcium channel (VGCC), CACNA1H, in sera of two HaNDL patients. CONCLUSION: Our results support the notion that ion channel autoimmunity might at least partially contribute to HaNDL pathogenesis and occurrence of neurological symptoms.